Olfactory Rod Cells: A Rare Cell Type in the Larval Zebrafish Olfactory Epithelium With a Large Actin-Rich Apical Projection - Cheung, King Yee; Jesuthasan, Suresh J.; Baxendale, Sarah; van Hateren, Nicholas J.; Marzo, Mar; Hill, Christopher J.; Whitfield, Tanya T. (Frontiers in Physiology, 2021)
We report the presence of a rare cell type, the olfactory rod cell, in the developing zebrafish olfactory epithelium. These cells each bear a single actin-rich rod-like apical projection extending 5–10 µm from the epithelial surface. Live imaging with a ubiquitous Lifeact-RFP label indicates that the olfactory rods can oscillate. Olfactory rods arise within a few hours of the olfactory pit opening, increase in numbers and size during larval stages, and can develop in the absence of olfactory cilia. Olfactory rod cells differ in morphology from the known classes of olfactory sensory neuron, but express reporters driven by neuronal promoters. A sub-population of olfactory rod cells expresses a Lifeact-mRFPruby transgene driven by the sox10 promoter. Mosaic expression of this transgene reveals that olfactory rod cells have rounded cell bodies located apically in the olfactory epithelium and have no detectable axon. We offer speculation on the possible function of these cells in the Discussion.